THE EFFECT OF BLENDED LEARNING ASSISTED BY GOOGLE CLASSROOM ON MATHEMATICS LEARNING OUTCOMES - Indah Resti Ayuni Suri; Mujib Mujib; Desmaria Rosadi; Naura Syifa Salsabila (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This study was motivated by the low mathematics learning outcomes of students. Preliminary observations at MTs Muhammadiyah Sukarame showed that many eighth-grade students had not achieved the minimum mastery criteria (KKM). In addition, previous studies have reported that low student engagement and ineffective learning strategies contribute to poor mathematics learning outcomes. Therefore, an innovative learning model is needed. This study aimed to determine differences in mathematics learning outcomes between students taught using blended learning assisted by Google Classroom and those taught using conventional learning, based on students’ learning motivation levels. This study employed a quasi-experimental design with a population of 106 eighth-grade students at MTs Muhammadiyah Sukarame. The sample was selected using cluster random sampling. Data were collected through a mathematics learning outcomes test and a learning motivation questionnaire and analyzed using a two-way ANOVA test. The results showed that there was no interaction between the learning model and learning motivation (p-value = 0.848 > 0.05). However, students taught using blended learning assisted by Google Classroom achieved better mathematics learning outcomes compared to those taught using conventional learning. Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar matematika siswa. Hasil observasi awal di MTs Muhammadiyah Sukarame menunjukkan bahwa sebagian besar siswa kelas VIII belum mencapai Kriteria Ketuntasan Minimal (KKM). Selain itu, penelitian terdahulu juga menunjukkan bahwa rendahnya keterlibatan siswa dan kurang efektifnya strategi pembelajaran berkontribusi terhadap rendahnya hasil belajar matematika. Oleh karena itu, diperlukan inovasi dalam model pembelajaran. Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar matematika antara siswa yang diajar menggunakan blended learning berbantuan Google Classroom dan siswa yang diajar menggunakan pembelajaran konvensional, ditinjau dari tingkat motivasi belajar siswa. Penelitian ini menggunakan desain quasi eksperimen dengan populasi seluruh siswa kelas VIII MTs Muhammadiyah Sukarame yang berjumlah 106 siswa. Sampel dipilih menggunakan teknik cluster random sampling. Data dikumpulkan melalui tes hasil belajar matematika dan angket motivasi belajar, kemudian dianalisis menggunakan uji ANOVA dua arah. Hasil penelitian menunjukkan bahwa tidak terdapat interaksi antara model pembelajaran dan motivasi belajar (p-value = 0,848 > 0,05). Namun demikian, siswa yang diajar menggunakan blended learning berbantuan Google Classroom memiliki hasil belajar matematika yang lebih baik dibandingkan dengan siswa yang diajar menggunakan pembelajaran konvensional.